MEDICINALLY IMPORTANT PLANT CLEOME GYNANDRA: A PHYTOCHEMICAL AND PHARMACOLOGICAL EXPLANATION - Adhikari, Partha Pradip; Paul, Satya Bhusan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Cleome genus includes 601 plant species from the family Cleomaceae. Of more than 600 plants, 206 (34.3%) plants are having accepted species names. Cleome gynandra Linn. is a well-known medicinal plant with traditional and pharmacological importance. A good number of secondary plant metabolites have also been isolated from different parts of C. gynandra. Our investigation confirms two mutant varieties of C. gynandra exists in India. Accordingly, the objective of this study was designed to critically evaluate the pharmacological and phytochemical evaluation of C. gynandra of two mutant variety, to provide a consolidated platform for research potential of both the mutant varieties of C. gynandra. Careful scrutiny reveals that the plant possesses a huge range pharmacological applications, such as anti-inflammatory, free radical scavenging, anticancerous, immunomodulator, and antidiabetic agents. To arrive its pharmacological importance the published papers also shown an enormous amount of phytochemicals endorsement. Scientific perusal reveals different parts of the plant has an immense medicinal importance which proofs its traditional use round the glove. But in North-Eastern region of India, the same plant abundantly found in pink mutant variety. To date, there is not much research investigation for this mutant variety to validate its pharmacological importance. Therefore, research needs to scrutinize and compare the medicinal claims of the pink mutant variety in the bio-diverse region of North-East India.